CON-type zeolite, method for producing CON-type zeolite, and method for producing lower olefins

JP7636213B2Active Publication Date: 2025-02-26MITSUBISHI CHEM CORP +2
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021039631
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-13
Filing Date
2021-03-11
Publication Date
2025-02-26
Estimated Expiration
2041-03-11

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、触媒として長寿命化を達成できるCON型ゼオライトを提供することができる。また、触媒として長寿命化を達成できるCON型ゼオライトを製造する方法を提供することができる。更には、当該ゼオライトを触媒として用いた低級オレフィンの製造方法を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636213000002
    Figure 0007636213000002
  • Figure 0007636213000003
    Figure 0007636213000003
  • Figure 0007636213000001
    Figure 0007636213000001
Patent Text Reader

Abstract

To provide a CON type zeolite that can achieve a long service life as a catalyst.SOLUTION: A CON type zeolite has, in nitrogen adsorption-desorption measurement, the ratio of a BET specific surface area (A2) calculated by BET plot to an external surface area (A1) calculated by t plot (A2 / A1) of 10 or less, and has a BET specific surface area (A2) of 620 m2 / g or more. Alternatively, the CON type zeolite has (A2 / A1) of 7 or less and the BET specific surface area (A2) of 400 m2 / g or more.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a CON type zeolite, more particularly to a CON type zeolite that can achieve a long life when used as a catalyst, and to a method for producing lower olefins using the zeolite as a catalyst. [Background technology]

[0002] Conventional methods for producing lower olefins such as ethylene, propylene, and butene include steam cracking of naphtha and fluid catalytic cracking of vacuum diesel. In recent years, metathesis reactions using ethylene and 2-butene as raw materials and the MTO (methanol to olefins) process using methanol and / or dimethyl ether as raw materials have become well known.

[0003] For example, as disclosed in Patent Document 1, by using methanol and / or dimethyl ether as raw materials and a catalyst containing a zeolite having a CON structure (CIT-1 zeolite) as an active component, propylene and butene can be produced in high yields, and further, the by-production of ethylene during propylene production can be suppressed.

[0004] In addition, Patent Document 2 describes Al as a CON-type zeolite catalyst that can maintain a high raw material conversion rate for a long period of time. 27 CON-type zeolites with signal intensities within a specific range in -MAS-NMR measurements have been proposed.

[0005] In addition, for example, Patent Documents 3 and 4 and Non-Patent Document 1 report that zeolite is mesostructured by hot water treatment in a pH-controlled medium in the presence of a surfactant, and that the feed conversion rate and the selectivity of components such as gasoline are increased in the catalytic cracking of crude oil. However, there is no mention of application to CON-type zeolites or the catalyst life in the production of lower olefins. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2013-245163 A [Patent Document 2] International Publication No. 2017 / 090751 [Patent Document 3] U.S. Patent No. 7,589,041 [Patent Document 4] Patent No. 5481027 [Non-patent literature]

[0007] [Non-Patent Document 1] Catal.Sci.Technol., 2, 987-994(2012) Summary of the Invention [Problem to be solved by the invention]

[0008] Patent Documents 1 and 2 disclose that lower olefins can be produced in high yields and that a high raw material conversion can be maintained. However, the life of CON-type zeolite as a catalyst is not necessarily sufficient, and it is necessary to frequently switch between reaction gas and regeneration gas for catalyst regeneration. The present invention is devised to solve the above problems, and an object of the present invention is to provide a CON-type zeolite that can achieve a long catalyst life. [Means for solving the problem]

[0009] The present inventors have conducted studies to solve the above problems and have found that it is possible to provide a CON type zeolite that can achieve a long catalyst life by optimizing the ratio of the BET specific surface area (A2) to the external surface area (A1) of the CON type zeolite, thereby completing the present invention.

[0010] The present invention includes the following gist. [1] In a nitrogen adsorption / desorption measurement, the ratio (A2 / A1) of the BET specific surface area (A2) calculated by the BET plot to the external surface area (A1) calculated by the t plot is 10 or less, and the BET specific surface area (A2) is 620 m 2 / g or more. [2] In the nitrogen adsorption / desorption measurement, the ratio (A2 / A1) of the BET specific surface area (A2) calculated by the BET plot to the external surface area (A1) calculated by the t plot is 7 or less, and the BET specific surface area (A2) is 400 m 2 / g or more. [3] The CON-type zeolite according to [1] or [2], which contains silicon (Si) and aluminum (Al) as constituent elements. [4] The CON-type zeolite according to [3], wherein the molar ratio (Si / Al) of silicon (Si) to aluminum (Al) is 10 or more. [5] A method for producing a CON-type zeolite, comprising the steps of: A method for producing CON-type zeolite, comprising an alkali treatment step of treating CON-type zeolite under alkaline conditions in the presence of a surfactant. [6] A method for producing a CON-type zeolite, comprising the steps of: A method for producing CON-type zeolite, comprising adding a surfactant to a raw material gel for zeolite synthesis. [7] The CON-type zeolite according to any one of [1] to [4], which is a catalyst used in a reaction for producing lower olefins. [8] A method for producing lower olefins, comprising a step of contacting a raw material containing methanol and / or dimethyl ether with the CON-type zeolite according to any one of [1] to [4] and [7].

[0011] In this specification, the term "lower olefin" refers to ethylene, propylene, and butene, in other words, olefins having 2 to 4 carbon atoms. Effect of the Invention

[0012] According to the present invention, it is possible to provide a CON type zeolite capable of achieving a long life as a catalyst. It is also possible to provide a method for producing a CON type zeolite capable of achieving a long life as a catalyst. Furthermore, it is also possible to provide a method for producing lower olefins using the zeolite as a catalyst. [Brief description of the drawings]

[0013] [Figure 1] 1 is a graph showing adsorption / desorption isotherms of CON-type zeolites according to Examples and Comparative Examples. For ease of viewing the graphs, the vertical axis is +500, +400, +300, +200, +100 [ml(STP) / g] for Examples 1 to 3 and Comparative Examples 1 and 2, respectively. The adsorption side is represented by a filled marker, and the desorption side is represented by an unfilled marker. [Diagram 2] 1 is a graph showing the transition of methanol conversion in the production of lower olefins using the CON-type zeolites according to the Examples and Comparative Examples as catalysts. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below. However, the description of the constituent elements described below is one example (representative example) of an embodiment of the present invention, and the present invention is not limited to these contents, and can be implemented in various modifications within the scope of the gist of the present invention.

[0015] One embodiment of the present invention is a CON-type zeolite, which has a ratio (A2 / A1) of the BET specific surface area (A2) calculated by a BET plot to the external surface area (A1) calculated by a t plot in a nitrogen adsorption / desorption measurement of 10 or less, and a BET specific surface area (A2) of 620 m 2 / g or more. Another embodiment of the present invention is a CON-type zeolite, which has a ratio (A2 / A1) of the BET specific surface area (A2) calculated by a BET plot to the external surface area (A1) calculated by a t plot in a nitrogen adsorption / desorption measurement, of 7 or less, and the BET specific surface area (A2) is 400 m 2 / g or more.

[0016] CON-type zeolite is a zeolite with a three-dimensional pore structure in which two 12-membered ring structures and one 10-membered ring structure intersect as its constituent units. Compared with CHA-type zeolite, which is composed of only 8-membered ring structures, and MFI-type zeolite, which is composed of only 10-membered ring structures, the CON-type zeolite with this 12-membered ring structure has an advantage in the diffusion of reaction products in the pores. In addition, since the CON-type zeolite has a structure in which the 12-membered ring structure and the 10-membered ring structure intersect in a zigzag pattern and the pores in three directions do not intersect at one point, the intersection space is small, coke due to the reaction is unlikely to be generated, and it is thought that the reaction activity is unlikely to decrease significantly, and the catalyst has the advantage of a long life.

[0017] In the present embodiment, the CON-type zeolite has a ratio (A2 / A1) of the BET specific surface area (A2) calculated by a BET plot to the external surface area (A1) calculated by a t plot in a nitrogen adsorption / desorption measurement of 10 or less, and a BET specific surface area (A2) of 620 m 2 / g or more, (A2 / A1) is 7 or less, and the BET specific surface area (A2) is 400 m 2 / g or more. By having the BET specific surface area (A2) be equal to or greater than the above lower limit, sufficient catalytic efficiency can be obtained. Specifically, the BET specific surface area (A2) is 400 m 2 / g or more, in which case it is preferably 500m 2 / g or more, more preferably 550m 2 / g or more, more preferably 600m 2 / g or more, and the BET specific surface area (A2) is 620 m 2 / g or more, in which case it is preferably 630m 2 / g or more, more preferably 640m 2 / g or more. The upper limit is not particularly limited, but is usually 2000m 2 / g or less.

[0018] In addition, when the ratio (A2 / A1) of the BET specific surface area (A2) to the external surface area (A1) is equal to or less than the upper limit, the catalytic function of the CON zeolite is extended. (A2 / A1) may be 10 or less, in which case it is preferably 9.5 or less, and may be 7 or less, in which case it is preferably 6 or less, more preferably 5 or less, and particularly preferably 4 or less. The lower limit is not particularly limited, but is usually 2 or more.

[0019] The BET specific surface area (A2), the ratio (A2 / A1) of the BET specific surface area (A2) to the external surface area (A1), and the micropore volume (A3) can be calculated from nitrogen adsorption / desorption measurements, and can be performed using, for example, the Belsorp-miniII manufactured by Microtrack-Bell. Data analysis can be performed using the analysis software BELMaster manufactured by Microtrack-Bell. Here, the BET specific surface area (A2) is calculated by BET plotting the measurement data with a relative pressure (P / P0) of 0.002 to 0.06. The external surface area (A1) and the micropore volume (A3) are calculated by t-plotting the data with a relative pressure (P / P0) of 0.20 to 0.42. The standard isotherm is Harkins-Jura.

[0020] The above value of (A2) and (A2 / A1) can be set within a specific range, for example, by using CON type zeolite as seed crystals or by including an alkali treatment step in which CON type zeolite is treated under alkaline conditions in the presence of a surfactant in the production process of CON type zeolite, as will be described later.

[0021] In this embodiment, the CON-type zeolite is not particularly limited as long as it satisfies the above values ​​of (A2) and (A2 / A1), but is preferably a crystalline metallosilicate. The elements constituting the metallosilicate are not particularly limited, but may include one or more elements selected from aluminum (Al), boron (B), titanium (Ti), vanadium (V), iron (Fe), zinc (Zn), gallium (Ga), germanium (Ge), zirconium (Zr), and tin (Sn).

[0022] Specifically, crystalline aluminosilicates containing Al as a constituent element and crystalline gallosilicates containing Ga are preferred. These zeolites have excellent catalytic activity because Al and Ga in the zeolite framework become acid sites and act as active sites for catalytic reactions. In particular, aluminosilicates containing Al are more desirable from the viewpoint of catalytic activity.

[0023] In addition, since the CON-type zeolite can be easily obtained by adding a boron compound to the raw material gel described later, it may contain B (boron) as a constituent element. Examples of such zeolite include crystalline boroaluminosilicate containing Al and B as constituent elements, and crystalline galloborosilicate containing Ga and B as constituent elements.

[0024] In the case of the crystalline aluminosilicate and crystalline gallosilicate, the ratio of the constituent elements is not particularly limited, but the Si / Al molar ratio or the Si / Ga molar ratio is usually 5 or more, preferably 10 or more, more preferably 25 or more, even more preferably 50 or more, particularly preferably 100 or more, and particularly preferably 200 or more, and is usually 5000 or less, preferably 1000 or less, and more preferably 500 or less. By setting the Si / Al molar ratio or the Si / Ga molar ratio in such a range, a zeolite catalyst having sufficient catalytic activity and further improved catalyst life can be obtained.

[0025] In the case of the crystalline boroaluminosilicate and the crystalline galloborosilicate, the ratio of the constituent elements is not particularly limited, but like the crystalline aluminosilicate and the crystalline gallosilicate, the Si / Al molar ratio or the Si / Ga molar ratio is usually 5 or more, preferably 10 or more, more preferably 25 or more, even more preferably 50 or more, particularly preferably 100 or more, and particularly preferably 200 or more, and is usually 5000 or less, preferably 1000 or less, and more preferably 500 or less. In addition, the Si / B molar ratio is not particularly limited, but is usually 3 or more, preferably 5 or more, more preferably 10 or more, and even more preferably 20 or more, and the upper limit may be, for example, 100000 or less, 50000 or less, or 10000 or less. The contents of Si, Al, Ga, B, etc. in this embodiment can usually be measured by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0026] The ion exchange sites of the CON-type zeolite are not particularly limited, and may be H-type or may be exchanged with metal ions. Specifically, the metal ions are alkali metal ions, alkaline earth metal ions, etc.

[0027] The micropore volume (A3) of the CON type zeolite used in this embodiment is not particularly limited, and is usually 0.1 ml / g or more, preferably 0.15 ml / g or more, more preferably 0.20 ml / g or more, and is usually 3 ml / g or less, preferably 2 ml / g or less.

[0028] The average particle size of the CON-type zeolite used in the present embodiment is not particularly limited, but is usually 3 μm or less, preferably 1 μm or less, more preferably 700 nm or less, and particularly preferably 300 nm or less. Also, it is usually 20 nm or more, and preferably 40 nm or more.

[0029] Hereinafter, a method for producing the CON type zeolite of the present embodiment will be described. CON type zeolite can generally be prepared by hydrothermal synthesis. For example, a boron source, an aluminum source, a gallium source, a silica source, and the like are added to water to generate a uniform gel, to which a structure directing agent, preferably N,N,N-trimethyl-(-)-cis-myrtanylammonium hydroxide, is added and stirred, and the obtained raw gel is crystallized by holding it at 120 to 200°C in a pressurized heating vessel. During crystallization, seed crystals may be added as necessary, and in terms of manufacturability, the addition of seed crystals is preferable in terms of improving operability. As the seed crystals, it is preferable to use CON type zeolite. In addition, it is preferable to add a surfactant to the raw gel. By adding a surfactant, the zeolite becomes fine particles, and the value of (A2) and the value of (A2 / A1) can be easily adjusted to the desired range. As the surfactant, cationic surfactants, anionic surfactants, nonionic surfactants, amphoteric surfactants, and the like can be used alone or in combination. The surfactant is preferably a cationic surfactant that acts as a moderate crystal growth inhibitor, and examples thereof include hexadecyltrimethylammonium bromide and hexadecyltrimethylammonium chloride. The concentration of the surfactant is not particularly limited, but the molar ratio to Si is preferably 0.001 to 0.05. The crystallized raw gel is then filtered and washed, and the solid content is dried at 100 to 200°C, and subsequently calcined at 400 to 900°C to obtain zeolite powder. Conventionally, CON-type zeolites have a slow nucleation and crystal growth rate, and have been synthesized over a relatively long period of time, about 5 to 21 days, so surfactants such as hexadecyltrimethylammonium bromide have not been introduced. This is because it has been thought that surfactants inhibit crystal growth, making crystallization difficult when surfactants are added. In this embodiment, the synthesis conditions are optimized to enable crystallization in a practical time, and the values ​​of (A2) and (A2 / A1) can be set in ranges that have not been achieved before, resulting in an especially excellent long life as a catalyst.

[0030] Here, one or more of boric acid, sodium borate, boron oxide, etc. can be used as the boron source. One or more of aluminum sulfate, aluminum nitrate, pseudoboehmite, aluminum alkoxide, aluminum hydroxide, alumina sol, sodium aluminate, etc. can be used as the aluminum source. One or more of gallium nitrate, gallium sulfate, gallium phosphate, gallium chloride, gallium bromide, gallium hydroxide, etc. can be used as the gallium source. One or more of silicates such as fumed silica, silica sol, silica gel, silicon dioxide, and water glass, silicon alkoxides such as tetraethoxyorthosilicate and tetramethoxysilane, silicon halides, etc. can be used as the silica source.

[0031] The amount of metal contained in CON-type zeolite can be adjusted by adjusting the amount of constituent elements (Al, Ga, B, etc.) during synthesis. It is also possible to use zeolites in which the content is adjusted by removing some of the constituent elements by steaming or acid treatment.

[0032] In this embodiment, it is preferable to have an alkali treatment step in which the prepared CON-type zeolite is treated with an alkali in the presence of a surfactant. The alkali treatment step causes the zeolite to have a mesostructure, making it easier to adjust the value of (A2) and the value of (A2 / A1) to the desired range. The surfactant used in the alkaline treatment step is a cationic surfactant or an anionic surfactant. The surfactant may be selected from the group consisting of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, and the like. In the alkali treatment step, the concentration of the surfactant is not particularly limited, and it may be contained in the treatment liquid at about 0.1 to 10% by mass.

[0033] The alkali for the alkali treatment is not particularly limited, and an ammonia solution, a sodium hydroxide solution, or the like can be used. The level of alkali is also not particularly limited, and it is sufficient that the pH is about 9 to 12, for example. The alkali treatment may be carried out by contacting the CON-type zeolite with an alkali, or by stirring the zeolite in an alkali solution. The temperature of the alkali treatment is not particularly limited, and may be, for example, about 100 to 200° C. The time of the alkali treatment is not particularly limited, and the zeolite may be immersed in the alkali solution for 0.1 to 24 hours. After the alkali treatment, it is preferable to dry the product and then calcinate it again for use as a catalyst to remove the incorporated surfactant.

[0034] The CON-type zeolite of the present embodiment can be used as a catalyst. When used as a catalyst, it may be a mixture with other substances, for example, compounds containing alkaline earth metals or silicon.

[0035] The CON-type zeolite of the present embodiment is used as a catalyst for producing lower olefins. The raw material may be methanol or dimethyl ether, but is not limited thereto, and may be appropriately selected depending on the type of the target olefin. There is no particular limitation on the origin of methanol and dimethyl ether. For example, they can be obtained by hydrogenation of a mixed gas of hydrogen / CO derived from coal and natural gas, and by-products in the steel industry, by reforming of alcohols derived from plants, by fermentation, or from organic materials such as recycled plastics and urban waste. In this case, they can be used as they are, or they can be purified, in a state where compounds other than methanol and dimethyl ether are mixed as they are, resulting from each production method. As the reaction raw material, only methanol or only dimethyl ether may be used, or a mixture of these may be used. When a mixture of methanol and dimethyl ether is used, there is no limitation on the mixing ratio.

[0036] The process for producing lower olefins using the above catalyst and raw material will be described below by taking as an example a case in which the raw material is methanol and / or dimethyl ether. Another embodiment of the present invention, a method for producing lower olefins, comprises a step of contacting a raw material containing methanol and / or dimethyl ether with the above-mentioned CON-type zeolite. The reaction mode in this embodiment is not particularly limited as long as the methanol and / or dimethyl ether feedstock is in the gas phase in the reaction zone, and a known gas phase reaction process using a fluidized bed reactor, a moving bed reactor, or a fixed bed reactor can be applied. The fixed bed reactor is advantageous in terms of equipment costs including auxiliary equipment, catalyst costs, and operation management. The process may be carried out in any of a batch, semi-continuous or continuous manner, but is preferably carried out in a continuous manner, and may be a process using a single reactor or a process using multiple reactors arranged in series or parallel.

[0037] When the above-mentioned catalyst is packed into the fluidized bed reactor, in order to minimize the temperature distribution in the catalyst layer, granular materials inactive to the reaction, such as quartz sand, alumina, silica, silica-alumina, etc., may be mixed with the catalyst and packed. In this case, there is no particular restriction on the amount of granular materials inactive to the reaction, such as quartz sand, used. In addition, the granular materials should have a particle size similar to that of the catalyst in order to ensure uniform mixing with the catalyst. It is preferable that Furthermore, the reaction substrates (reaction raw materials) may be divided and fed to the reactor for the purpose of dispersing heat generated by the reaction.

[0038] Although there is no particular limitation on the total concentration (substrate concentration) of methanol and dimethyl ether in all the components fed to the reactor, the sum of methanol and dimethyl ether is preferably 90 mol % or less, more preferably 10 mol % or more and 70 mol % or less, in all the components fed.

[0039] In addition to methanol and / or dimethyl ether, the reactor may contain gases inert to the reaction (also referred to as diluents), such as helium, argon, nitrogen, carbon monoxide, carbon dioxide, hydrogen, water, paraffins, hydrocarbons such as methane, aromatic compounds, and mixtures thereof. Among these, the coexistence of water (water vapor) is preferred because it is easily separated. As such a diluent, impurities contained in the reaction raw materials may be used as they are, or a separately prepared diluent may be mixed with the reaction raw materials. The diluent may also be mixed with the reaction raw materials before being placed in the reactor, or may be supplied to the reactor separately from the reaction raw materials.

[0040] The lower limit of the reaction temperature is usually about 200°C or higher, preferably 250°C or higher, more preferably 300°C or higher, and the upper limit of the reaction temperature is usually 750°C or lower, preferably 700°C or lower. If the reaction temperature is too low, the reaction rate is low, and a large amount of unreacted raw materials tends to remain, and the yield of low olefins also decreases. On the other hand, if the reaction temperature is too high, it is difficult to obtain stable catalyst activity, and the yield of low olefins decreases significantly. Here, the reaction temperature refers to the temperature at the inlet of the catalyst layer.

[0041] The upper limit of the reaction pressure is usually 5 MPa (absolute pressure, the same applies below), preferably 2 MPa, more preferably 1 MPa, and particularly preferably 0.7 MPa. The lower limit of the reaction pressure is not particularly limited, but is usually 0.1 kPa or more, preferably 7 kPa or more, and more preferably 50 kPa or more. If the reaction pressure is too high, the amount of undesirable by-products such as paraffins and aromatic compounds produced increases, and the yield of lower olefins tends to decrease. If the reaction pressure is too low, the reaction rate tends to be slow.

[0042] The reactor outlet gas (reactor effluent) is a mixed gas containing lower olefins as the reaction product, by-products and a diluent. The concentration of lower olefins in the mixed gas is usually 5 to 95% by weight. Although the reaction product contains methanol and / or dimethyl ether as unreacted raw materials depending on the reaction conditions, it is preferable to carry out the reaction under reaction conditions that result in a 100% conversion of methanol and / or dimethyl ether, which makes it easy, and preferably unnecessary, to separate the reaction product from the unreacted raw materials. By-products include olefins having 5 or more carbon atoms, paraffins, aromatic compounds and water.

[0043] The reactor outlet gas, which is a mixed gas containing lower olefins as the reaction product, unreacted raw materials, by-products and diluents, may be introduced into a known separation and purification facility and may be recovered, purified, recycled or discharged according to the respective components.

[0044] In addition, the applications of the zeolite catalyst of the present invention are not limited to the production of lower olefins, and the catalyst can be suitably used for the production of p-xylene, ethylbenzene, and cumene, aromatization of light hydrocarbons, hydrocracking, hydrodewaxing, alkane isomerization, and automobile exhaust gas purification, etc. EXAMPLES

[0045] The present invention will be described in more detail below with reference to examples, but it goes without saying that the scope of the present invention is not limited to the examples.

[0046] [Example 1] 0.050g of sodium hydroxide, 2.85g of 30.0wt% N,N,N-trimethyl-(-)-cis-myrtanylammonium hydroxide aqueous solution, and 2.90g of demineralized water were mixed, and 0.050g of boric acid and 0.016g of aluminum sulfate were added and stirred, and then 3.97g of Cataloid SI-30 was added as a silica source and stirred thoroughly. Furthermore, 0.024g of CON type zeolite (Si / Al=270) was added as a seed crystal, and stirred to prepare a raw gel.

[0047] The obtained raw gel was placed in an autoclave and heated at 170°C for 5 days at 15 rpm. The product was filtered, washed with water, and then dried at 100°C to obtain a white powder. From the X-ray diffraction (XRD) pattern of the product, it was confirmed that the product was CON-type zeolite. After drying, it was calcined in an air atmosphere at 600°C for 6 hours to obtain a sodium-type zeolite powder.

[0048] The obtained powder was subjected to ion exchange in a 1N ammonium nitrate aqueous solution at 80°C for 1 hour, and then filtered. The filtered powder was again subjected to ion exchange in a 1N ammonium nitrate aqueous solution at 80°C for 1 hour, and then filtered and dried to obtain an ammonium type zeolite powder. Then, the powder was calcined in an air atmosphere at 500°C for 6 hours to obtain the proton type zeolite powder of Example 1.

[0049] [Example 2] 0.200 g of the proton-type zeolite obtained in Example 1, 0.140 g of hexadecyltrimethylammonium bromide, 11.99 g of desalted water, and 0.81 g of 10% aqueous ammonia were mixed and thoroughly stirred. The obtained slurry was charged into an autoclave and heated at 150°C for 7 hours while standing. The product was filtered, washed with water, and then dried at 100°C to obtain a white powder. After drying, it was calcined at 600°C for 6 hours in an air atmosphere to obtain the zeolite powder of Example 2.

[0050] [Example 3] 5.522g of 30.9wt% N,N,N-trimethyl-(-)-cis-myrtanylammonium hydroxide solution, 0.642g of 8M sodium hydroxide solution, and 17.321g of demineralized water were mixed, and 0.247g of boric acid and 0.026g of aluminum sulfate were added and stirred, and then 2.404g of Cab-O-sil M7D was added as a silica source and stirred thoroughly. 0.146g of hexadecyltrimethylammonium bromide was further added and stirred, and then 0.049g of CON type zeolite (Si / Al=270) was added as a seed crystal and stirred to prepare a raw gel. The obtained raw gel was placed in an autoclave and heated at 170°C for 7 days at 40 rpm. The product was filtered, washed with water, and then dried at 100°C to obtain a white powder. After drying, it was calcined at 600°C for 6 hours in an air atmosphere to obtain a sodium-type zeolite powder. The obtained powder was subjected to ion exchange in a 2.5N ammonium nitrate aqueous solution at 80°C for 2 hours, then filtered and dried. The dried powder was again subjected to ion exchange in a 2.5N ammonium nitrate aqueous solution at 80°C for 3 hours, then filtered and dried to obtain an ammonium type zeolite powder. The powder was then calcined in an air atmosphere at 600°C for 3 hours to obtain a proton type zeolite powder of Example 3.

[0051] [Comparative Example 1] 1.29 g of 1.0 M sodium hydroxide solution, 2.88 g of 30.0 wt% N,N,N-trimethyl-(-)-cis-myrtanylammonium hydroxide solution, and 1.67 g of salt water was mixed, 0.049 g of boric acid and 0.010 g of aluminum sulfate were added thereto and stirred, and then 4.02 g of Cataloid SI-30 was added as a silica source and thoroughly stirred. 0.025 g of BEA type zeolite (Si / Al=20) was further added as seed crystals and stirred to prepare a raw gel. The obtained raw gel was heated and post-treated in the same manner as in Example 1 to obtain a proton type zeolite powder of Comparative Example 1.

[0052] [Comparative Example 2] 0.052g of sodium hydroxide, 2.77g of 30.8wt% N,N,N-trimethyl-(-)-cis-myrtanylammonium hydroxide aqueous solution, and 3.00g of demineralized water were mixed, and 0.049g of boric acid and 0.008g of aluminum sulfate were added thereto and stirred, and then 3.93g of Cataloid SI-30 was added as a silica source and stirred thoroughly. Furthermore, 0.024g of BEA type zeolite (Si / Al=15) was added as seed crystals and stirred to prepare a raw material gel. The obtained raw material gel was heated and post-treated in the same manner as in Example 1 to obtain a proton type zeolite powder of Comparative Example 2.

[0053] [Comparative Example 3] 0.45g of 1.0M sodium hydroxide solution, 0.79g of 1.05M N,N-trimethyl-(-)-cis-myrtanylammonium hydroxide solution, and 1.43g of demineralized water were mixed, to which 0.011g of boric acid and 0.0082g of zinc acetate were added and stirred, after which 0.27g of fumed silica (Cab-O-Sil M-7D, manufactured by CABOT) was added as a silica source and thoroughly stirred. 0.0054g of BEA-type borosilicate was further added as seed crystals and stirred to prepare a raw gel. The obtained raw gel was placed in an autoclave and heated at 170°C for 7 days at 40 rpm. The product was filtered, washed with water, and then dried overnight at 100°C. After drying, it was calcined at 600°C for 6 hours in an air atmosphere to obtain a sodium-type zeolite powder.

[0054] 0.2 g of the obtained powder was added to 20 ml of a 2N aqueous solution of nitric acid and stirred at 100°C under reflux for 20 hours. The zeolite was then filtered, washed with water, and dried overnight at 100°C to obtain a proton-type zeolite powder. The entire amount of the obtained powder was added to 20 g of an aqueous solution in which 0.0031 g of aluminum nitrate nonahydrate had been dissolved, and stirred for 2 days at 100°C under reflux. The zeolite was then filtered, washed with water, and dried overnight at 100°C to obtain a proton-type zeolite powder of Comparative Example 3.

[0055] The synthesis conditions for Examples 1 to 3 and Comparative Examples 1 to 3 are summarized in Table 1. Comparative Examples 1 and 2 are examples in which the feed composition is the same as that of Example 1 except that the seed crystals were changed from CON type zeolite to BEA type zeolite.

[0056] The zeolites according to Examples 1 to 3 and Comparative Examples 1 to 3 were evaluated as follows. <Nitrogen adsorption / desorption measurement> Nitrogen adsorption and desorption measurements of the synthesized proton-type zeolite powder were performed using a Belsorp-mini II manufactured by Microtrack-Bell. In the measurement, the zeolite was heated and dried at 400°C under vacuum for 2 hours, and then nitrogen adsorption and desorption measurements were performed at liquid nitrogen temperature. Figure 1 shows the adsorption and desorption isotherms of the zeolites according to Examples 1 and 2 and Comparative Examples 1 to 3. Data analysis was performed using analysis software BELMaster manufactured by Microtrack-Bell. The BET specific surface area (A2) was calculated by BET plotting the measurement data with relative pressures (P / P0) of 0.002 to 0.06. The external surface area (A1) and micropore volume (A3) were calculated by t-plotting the data with relative pressures (P / P0) of 0.20 to 0.42. The standard isotherm used was Harkins-Jura.

[0057] <Production of lower olefins> The zeolites obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were used to produce lower olefins. A fixed-bed flow reactor was used for the reaction, and 33 mg of premixed proton-type zeolite powder and 470 mg of quartz sand were filled in a quartz reaction tube with an inner diameter of 6 mm. A mixed gas of 50 mol % methanol and 50 mol % nitrogen was introduced at a weight hourly space velocity of methanol of 15 h 2 -1 The mixture was fed to the reactor so that the reaction was carried out at 500°C and 0.1 MPa (absolute pressure). The products were analyzed by gas chromatography every hour from the start of the reaction. Figure 2 shows a graph showing the progress of the methanol conversion rate. Table 1 shows the methanol conversion rate (%), ethylene selectivity (C-mol%), propylene selectivity (C-mol%), butene selectivity (C-mol%) and catalyst life (hr) two hours after the reaction. The catalyst life was defined as the time during which the methanol conversion rate was maintained at 99% or more.

[0058] As shown in Table 1, the ratio (A2 / A1) of the BET specific surface area (A2) to the external surface area (A1) is small, and the zeolites of Examples 1 to 3 having a large BET specific surface area (A2) maintain a high raw material conversion rate for a long period of time.

[0059] [Table 1]

Claims

1. In a nitrogen adsorption / desorption measurement, the ratio (A2 / A1) of the BET specific surface area (A2) calculated by BET plot to the external surface area (A1) calculated by t plot is 10 or less, and the BET specific surface area (A2) is 620 m 2 / g or more, The molar ratio (Si / Al or Si / Ga) of the constituent elements silicon (Si) and aluminum (Al), or silicon (Si) and gallium (Ga) is 200 or more; CON type zeolite.

2. In a nitrogen adsorption / desorption measurement, the ratio (A2 / A1) of the BET specific surface area (A2) calculated by BET plot to the external surface area (A1) calculated by t plot is 7 or less, and the BET specific surface area (A2) is 400 m 2 / g or more, The molar ratio (Si / Al or Si / Ga) of the constituent elements silicon (Si) and aluminum (Al), or silicon (Si) and gallium (Ga) is 200 or more; CON type zeolite.

3. A method for producing the CON-type zeolite according to claim 1 or 2, comprising the steps of: The method includes an alkali treatment step of treating CON zeolite under alkaline conditions in the presence of a surfactant, An ammonia solution is used as the alkali for the alkaline treatment, The concentration of the surfactant in the treatment solution is 0.1 to 10% by mass, The temperature of the alkali treatment is 100 to 200°C. A method for producing CON type zeolite.

4. A method for producing the CON-type zeolite according to claim 1 or 2, comprising the steps of: A cationic surfactant is added to the zeolite synthesis raw material gel, The process includes a step of crystallizing the zeolite synthesis raw material gel by holding the gel at 120 to 200° C. in a pressurized and heated container, The concentration of the cationic surfactant is 0.001 to 0.05 in terms of a molar ratio to Si; A method for producing CON type zeolite.

5. The method for producing CON type zeolite according to claim 3 or 4, wherein the surfactant is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride.

6. 3. The CON-type zeolite according to claim 1 or 2, which is a catalyst used in a reaction for producing lower olefins.

7. A method for producing lower olefins, comprising a step of contacting a raw material containing methanol and / or dimethyl ether with the CON zeolite according to any one of claims 1, 2 and 6.

Citation Information

Patent Citations

  • Television signal identifying unit

    JP1979081027A

  • Synthesis of zeolites

    JP2003502267A

  • Mesostructured zeolite material, method for manufacturing the material, and method for using the material

    JP2007534589A

  • Zeolite nanosheets and similar materials having a framework thickness equivalent to the size of one single unit crystal lattice or the size of 10 or fewer single unit crystal lattices, arranged regularly or irregularly, in multiple or single-plate structures.

    JP2012530680A

  • Method for synthesizing alumina-containing mesoporous material and alumina-containing mesoporous material

    JP2013047166A